p-65/5=6

Simple and best practice solution for p-65/5=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p-65/5=6 equation:



p-65/5=6
We move all terms to the left:
p-65/5-(6)=0
determiningTheFunctionDomain p-6-65/5=0
We add all the numbers together, and all the variables
p-19=0
We move all terms containing p to the left, all other terms to the right
p=19

See similar equations:

| 3/4m=6.5 | | 1/2(w+2)=5 | | | | | | | | | | | | | | | | | | 2+7y=3-3y | | | | | | | | | | | | | | | | | | | | | | | | | | | | | | | | 2x+5x+15=12 | | k−–3=9 | | 65-y=y-65 | | -5r+-21=-51 | | 4(1-2x)=44 | | 5(j-4)+j=-18 |

Equations solver categories